ANALYSIS OF POTENTIAL HAZARDS FOR GADUNG CHIPS WORKERS USING THE HIRARC METHOD IN RINGINSARI VILLAGE KEDIRI REGENCY - Irianingtyas, Riza; Maryiantari, Ellyza Setya; Tigowati; Nuwa, Geovania Nage (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: One of the industrial sectors that has a high risk of danger is the informal sector, one of which is the home industry of making chips. Knowledge about occupational health and safety is one of the factors that cause health problems and incidents in the workplace. Therefore, it is necessary to handle the problem of danger by identifying risks and controlling in minimizing the occurrence of accidents and occupational health disorders. Objectives: The purpose of this research was to determine the risk of work accidents, determine the level of work accident risk and provide suggestions for controlling the risk of work accidents that can occur in the cassava chips manufacturing industry. Methods: This study is a descriptive observational study, which is a research method that provides an in-depth description of the process of making gadung chips in a home industry which is then analyzed and compared based on existing reality. Observations are made directly to ensure that the process reflects daily practices in the home industry. The study was conducted with a cross-sectional approach, data will be collected at one time to understand the conditions at that time. The data analysis technique used in this study is descriptive analysis and risk identification with the HIRARC method, namely: 1) Hazard identification, 2) Risk Assessment (Risk Analysis), 3) Determining Controls, 4) Documentation Socialization and Implementing Controls Results: 33 work accident risks were found that could occur in the process of making combined chips. The level of work accident risk from 33 risks obtained 42% low risk hazards, 21% medium risk hazards, 30% high risk hazards and 7% very high risk hazards Conclusion: Based on the research results, it can be concluded that: 1) 33 work accident risks were found that could occur in the process of making combined chips. 2) the level of work accident risk from 33 risks obtained 42% low risk hazards, 21% medium risk hazards, 30% high risk hazards and 7% very high risk hazards. 3) there are 33 risk control studies consisting of substitution control, administration, and use of PPE